2012
DOI: 10.1152/ajpgi.00266.2011
|View full text |Cite
|
Sign up to set email alerts
|

Lactobacillus reuteristrains reduce incidence and severity of experimental necrotizing enterocolitis via modulation of TLR4 and NF-κB signaling in the intestine

Abstract: Necrotizing enterocolitis (NEC) is the leading gastrointestinal cause of mortality and morbidity in the premature infant. Premature infants have a delay in intestinal colonization by commensal bacteria and colonization with potentially pathogenic organisms. Lactobacillus reuteri is a probiotic that inhibits enteric infections, modulates the immune system, and may be beneficial to prevent NEC. In previous studies, L. reuteri strains DSM 17938 and ATCC PTA 4659 differentially modulated inflammation in vitro; how… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
134
2
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 164 publications
(144 citation statements)
references
References 58 publications
5
134
2
3
Order By: Relevance
“…LR17938 inhibits pathogen growth and modulates the immune system. In this study the protective effects of the probiotic LR17938 on the survival, incidence, and severity of NEC in a mouse model further validated our previous observations in a rat NEC model (27,29). In addition, previous studies indicated that the frequency of gut Foxp3 ϩ Treg cells was decreased in NEC but reverted to normal following LR17938 treatment (27).…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…LR17938 inhibits pathogen growth and modulates the immune system. In this study the protective effects of the probiotic LR17938 on the survival, incidence, and severity of NEC in a mouse model further validated our previous observations in a rat NEC model (27,29). In addition, previous studies indicated that the frequency of gut Foxp3 ϩ Treg cells was decreased in NEC but reverted to normal following LR17938 treatment (27).…”
Section: Discussionsupporting
confidence: 87%
“…Two plasmids harboring antibiotic resistance genes were removed from strain 55730 to obtain strain 17938 (46), which inhibits pathogen growth and modulates the immune system. We have shown that feeding LR17938 to newborn rats produced a strong anti-inflammatory effect (28,29), reducing the incidence and severity of NEC (29) while increasing the frequency of Treg cells in the intestinal mucosa (27).…”
mentioning
confidence: 98%
“…Liu also verified that Roy's lactobacillus DSM 17938 rat NEC has a positive effect on the prevention on rat NEC, which can significantly reduce the mRNA expression of TNF alpha and TLR 4 and TNF alpha, TLR 4 protein levels (Liu et al, 2012). Rajput verified that boundens yeast and bacillus B10 stimulated chicken bone marrow dendritic cells, increasing TLR 1, TLR 2, TLR 4, and TLR 15 expression (Rajput et al, 2014).…”
Section: Bacillus Coagulans Enhance the Immune Function Of The Intestmentioning
confidence: 82%
“…However, alteration of gut flora is only one potential mechanism by which probiotics might prevent NEC. Other mechanisms include effects on the gut immune system and via TLR-related signaling [76,77] and effects on mucosal integrity and intestinal permeability [78,79]. However, whether these are primary or secondary effects is extremely difficult to dissect, as the microbiome, immune system, mucosal integrity and gut barrier function are all mutually interdependent.…”
Section: Mechanistic Basic Science Studies On Probioticsmentioning
confidence: 99%